The Effect of Good Governance, Accountability, and Transparency of Village Funds on Public Trust: Pengaruh Pemerintahan yang Baik, Akuntabilitas, dan Transparansi Dana Desa Terhadap Kepercayaan Masyarakat - Taufiqi, Dhafin; Ariani, Kurnia Rina (Universitas Muhammadiyah Sidoarjo, 2022)
Not all village governments can carry out their performance well in managing village funds, so that it can trigger public distrust of the village government in managing village funds. This study aims to examine the effect of good governance, accountability and transparency of village funds on public trust. The research method used in this study is a quantitative method. The data used in this study is primary data with a questionnares and distributed to the community in Grudo village, Ngawi sub-district, Ngawi district. By using multiple linear regression analysis, this study shows that the village fund accountability variable has a significant effect on public trust, but the good governance variable and the village fund transparency variable has no significant effect on public trust. Based on the research findings, village funds accountability is an important factor to increase public trust in village government.